Implementation of Digital Libraries in Book Management and Donation in the Nyala Aksara Community - Saut Pintubipar Saragih; Mesri Silalahi (CESS (Journal of Computer Engineering, System and Science), 2023)
Web Based Applications has been implemented to organize bookstore and it is reuired to handle a wider library system, especially in a non-profit organization such as Nyala Aksara community library in Batam City. All library sources especially book collections come from donations from the community or charity, with this situation it is expected for the commitee to be able provide a system to reach more people to donate with easiness. The E-library Web application is expected to be able to provide solutions for the Nyala Aksara organization management. The main problems is the donations systems that have not been systematically organized, and then borrowing and returning system for users. E-library application will be built using web-based programming like HTML PHP, MySQL database and designing method with UML Method. The e-library will provide services for those who want to donate books, this application will also provide a system that is able to manage borrowers and how to process the book returning. The results of this research is producing a solution for the organization called E-libarary which is a web-based library management.